A comparative study of acrylic and epoxy-based adhesives for perovskite solar cells encapsulation - Soares, Gabriela A.; Bicalho, Izabela S.; Castro-Hermosa, Sergio; Corrêa, Luiza de Q.; Miranda, Bárbara H.S.; Marques, Adriano dos S.; Fernandes, Silvia L. [UNESP]; Cunha, Thainá; de Freitas, Vinícius V.; Vilaça, Rodrigo de Q.; Wouk, Luana; Bagnis, Diego (Elsevier, 2024)
The development of a reliable encapsulation is a key factor for protecting perovskite solar cells from extrinsic degradation and an important step to commercialization. The use of edge sealing materials has already been proven effective for rigid substrates. However, for flexible devices, a different encapsulation strategy must be developed. In this study, epoxy- and acrylic-based adhesives were tested over blade-coated p-i-n MAPI devices and the encapsulation was evaluated with current–voltage measurements, calcium, and thermal stability tests. Although causing discoloration around the cells, over the area without the evaporated top electrode, the epoxy adhesive showed great performance after encapsulation and under thermal stress. This strategy was used to compare the stability of PEDOT:PSS and NiO as HTL. After an initial drop of 40 % in performance, the device with NiO was stable for over 5500 h under 85 °C. These results show that this method can be used for evaluating the stability of perovskite solar cell and that, with further development of a proper buffer layer, epoxy-based adhesives are an effective strategy for flexible encapsulation.
Keywords: Acrylic; Encapsulation; Epoxy; Perovskite solar cell